Rockall Scale as a Predictor of Rebleeding and Mortality in Patients with Upper Gastrointestinal Bleeding of Non-variceal Origin - Reynolds P. Anderson, James G. Ava, Marie S. Anderson (Academic Journal of Clinicians, 2025)
Upper gastrointestinal bleeding remains a significant challenge among gastroenterologists and surgeons worldwide and it is recognized as a primary reason for hospital admissions, with an incidence ranging from 50 to 150 cases per 100,000 individuals in the USA, resulting in 200,000 to 300,000 hospitalizations annually, accompanied by a mortality rate of 5 to 10% in most studies. This has been linked to the consumption of NSAIDs among elderly patients (60% aged between 25 and 64 years), although certain studies indicate a decline to as low as 2%. Upper gastrointestinal bleeding is characterized by hemorrhage from a lesion situated above the angle of Treitz, presenting as hematemesis, coffee-colored vomit, or both, along with melena. Recent advancements in etiology, diagnosis, and therapy indicate that prompt and efficient initial intervention during the first few hours enhances prognosis. A delay in care correlates directly with death; thus, the implementation of prognostic scales is essential for identifying individuals at elevated risk of problems necessitating hospitalization and emergency endoscopy. The Rockall score has undergone prospective and external validation across many populations. Rockall score has been suggested as good predictor of hemorrhage and mortality and the Rockall score of 8 or higher was linked with higher rate of mortality and hemorrhage and those patients showed worse outcomes. Presently, research conducted are assessing the efficacy of the Rockall scale in stratifying mortality risk in patients with upper gastrointestinal hemorrhage. This study sought to assess the efficacy of the Rockall score in predicting death among patients with non-variceal upper gastrointestinal hemorrhage at the Veracruz High Specialty Hospital.